A Bourdieusian Analysis of the Sociocultural Capital of Chinese International Graduate Students in the United States - Wang, Xinxin; Freed, Rebekah (Journal of International Students, 2021)
For the last decade, Chinese international graduate students (CIGS) have represented the largest portion of international graduate students in the United States. Previous research studies on language barriers and cultural differences have revealed that CIGS experience difficulties in adapting to the American educational system (Zhang-Wu, 2018). Few researchers have critically examined the experiences of CIGS on a more organizational level. In this qualitative study, we analyzed interviews with CIGS utilizing a Bourdieusian (1986a) framework to identify the social and cultural capital (SCC) that CIGS possessed. We argue that SCC concepts can help theoretically and critically examine the experiences of international students as a minority student group in the United States. The results from our in-depth semistructured interviews imply that CIGS are excluded from access to and possession of the SCC necessary to adapt to academic, cultural, and social life in the United States.